(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This research addresses the topic of hate speech in Lebanon: the legal challenge of criminalization and the limits of protection against sectarian divisions. It is considered one of the contemporary legal and social issues that raises an ongoing debate regarding, on the one hand, the boundaries of freedom of expression in Lebanon, and on the other hand, the necessity of criminalizing incitement and discriminatory speech. This debate is further shaped by the Lebanese reality, which is characterized by political and sectarian diversity, making the regulation of such speech a particularly delicate and sensitive matter. The study begins by defining the legal concept of hate speech and distinguishing it from freedom of opinion and expression, while highlighting the boundaries between the legitimate exercise of freedom and its transformation into a tool for incitement or exclusion. It also examines the relevant national and international legal frameworks governing the fight against hate speech, emphasizing the adequacy of Lebanese legal provisions in complying with international obligations in this field. The research further analyzes the mechanisms adopted to address hate speech through prevention, protection, and criminalization measures, in addition to reviewing possible national strategies to limit its spread, particularly considering the growing influence of social media in expanding and accelerating its reach. Moreover, it discusses the consequences of hate speech, especially its impact on civil peace, social cohesion, and national stability, highlighting its serious threat to the structure of Lebanese society. The study concludes that addressing this phenomenon requires a balanced approach that combines strengthening the legal framework, promoting social awareness, and safeguarding freedom of expression, in order to protect society and reinforce a culture of peaceful coexistence.